Sunnah, Sains dan Peradaban Manusia; Menelaah Kembali Pemikiran Yusuf Al-Qardhawi - Putra, Ahmad; Rumondor, Prasetio (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2020)
In this era, a variety of thoughts emerged that led to problems in the field of science. So the study of Yusuf al-Qardhawi's thoughts is interesting to review again to provide a framework which relies on as Sunnah as the basis of the second Islamic law. This literature study aims to analyze Yusuf al Qardhawi's thoughts about the Sunnah as a source of science and human civilization. Furthermore this article is expected to reflect these thoughts in intellectual life. The author concludes that, for Yusuf al-Qardhawi, the Sunnah is a practical interpretation of the Qur'an and its ideal application in Islam. The Sunnah also provides a strong connection to the development of human civilization. The author argues, by making the Sunnah a source of knowledge and civilization, al-Qardhawi actually emphasizes the use of reason that refers to the Sunnah as a contextual source